(untitled) (Al-Academy, 2023)
This study reveals the impact of critical reading on viewers understanding and astatic judgment at artworks. And aims to find out the reasons and motives behind their issuing of these judgments towards artworks. The study adopts the qualitative method as two pre and post interviews were conducted and analysed according to a thematic analysis method. The results show that critical reading contributes to their understanding of the content of artworks and the message that the artist would like to convey to the recipient audience. and directs them towards the aesthetic judgment that is based on full understanding of the philosophical contents of the artwork, which, in turn, contributes to the development of artistic culture and artistic taste. the study recommends the need to conduct studies and research similar to the current study in order to develop the recipients’ potentials to understand artworks and judge them